Vaccines in cardiology, an underutilized strategy to reduce the residual cardiovascular risk - García-Zamora, Sebastián (2024)
Cardiovascular diseases stand as the leading cause of mortality among adults globally. For decades, comprehensive evidence has underscored the correlation between infections, particularly those involving the respiratory system, and an elevated risk of cardiovascular and cerebrovascular events, as well as all-cause mortality. The mechanisms through which infections heighten cardiovascular events are intricate, encompassing immune system activation, systemic inflammation, hypercoagulable states, sympathetic system activation, and increased myocardial oxygen demand. Respiratory infections further contribute hypoxemia to this complex interplay. These mechanisms intertwine, giving rise to endothelial dysfunction, plaque ruptures, myocardial depression, and heart failure. They can either instigate de novo cardiovascular events or exacerbate pre-existing conditions. Compelling evidence supports the safety of influenza, pneumococcal, herpes zoster, COVID-19 and respiratory syncytial virus vaccines in individuals with cardiovascular risk factors or established cardiovascular disease. Notably, the influenza vaccine has demonstrated safety even when administered during the acute phase of a myocardial infarction in individuals undergoing angioplasty. Beyond safety, these vaccinations significantly reduce the incidence of cardiovascular events in individuals with an augmented cardiovascular risk. Nevertheless, vaccination rates remain markedly suboptimal. This manuscript delves into the intricate relationship between infections and cardiovascular events. Additionally, we highlight the role of vaccinations as a tool to mitigate these occurrences and reduce residual cardiovascular risk. Finally, we emphasize the imperative need to optimize vaccination rates among individuals with heart diseases.